End-to-End Automated UI Testing Workflow for Web Sites with Intensive User-System Interactions - Oguz, Ramazan Faruk; Erdem, Izzettin; Olmezogullari, Erdi; Aktas, Mehmet S. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2022)
The user interface (UI) is the software component with which the end users interact the most in the mobile and web world today. Therefore, when evaluating end-user satisfaction with a software, besides the functional features, the possibilities provided by the UIs are significant. End-user interfaces offer several capabilities today, necessitating a complex structure. Examples include interfaces developed in technologies such as Google Flutter and React. Therefore, we foresee a need for UI testing business workflows allowing comprehensive testing of UIs to improve customer satisfaction. Within the scope of this research, we propose an end-to-end approached automated UI testing business workflow for testing UI components on websites with intense user actions.
Keywords: Automated UI testing; business workflow; end-user interface; comprehensive testing; Computer Science; Engineering